Aplicativo (prototipo) para la administración y estandarización de auditorías integrales internas en la preselección, evaluación y seguimiento de contratistas (2015)
In this document an application (prototype) is made for the selection, evaluation and monitoring of contractors under the parameters of internal integral audits, which will result in objective information for the control of contractors in the hydrocarbon sector in the drilling area. In addition, the document carries out the standardization of the selection, monitoring and evaluation by means of a model used by one of the companies in the hydrocarbon sector. On the other hand, the application has objective outputs (reports, statistics, dynamic tables, among other mathematical tools) for decision making by those responsible for the process and have solid criteria for decision making and establishing results of the review by management providing important data for continuous improvement. The application develops this process of selection of contractors based on the traceability of the audits carried out by the company and the current regulations of the sector. This information also provides parameters to establish the controls during the time of the contract, in addition to effectively evaluating them and avoiding bias due to the decision making of third parties. Finally the application is programmed in Visual Basic for applications, since the software allows agility and compatibility with any company that has the Office package in any of its versions, thus avoiding the long installation processes and availability of large computing platforms to establish the application In addition to being practical and lightweight achieving efficiency in data processing.